Improvement of part straightness accuracy in rough cutting of wire EDM through a mechatronic system design. Issue 9 (June 2016) - Yan, Mu-Tian; Wang, Pi-Wen; Lai, Jian-Cheng
Abstract This paper presents a mechatronic system approach to the improvement of part straightness accuracy in rough cutting of wire electrical discharge machining (wire EDM). The mechatronic system design integrated an active wire feed apparatus and a microcontroller-based wire tension control system into a novel wire transport system for providing a smooth wire transport and a constant wire tension value. The active wire feed apparatus was first devised to reduce the inertial effect of the wire spool on the wire transport system. Then, a proportional-integral-derivative (PID) controller was used to implement real-time wire tension control of the wire transport system. Compared to a typical wire transport system, steady-state error of wire tension control can be reduced by half using the newly developed system. Through pulse train analysis, the proportion of normal sparks to total sparks defined as normal spark ratio can be used to monitor spark gap condition as well as to be an indication of evaluating machining speed and part straightness accuracy. Experimental results show that part straightness accuracy can be significantly improved from 13 to 4 μm by the newly developed wire transport system along with optimum machining settings.